Analisis Penataan Tempat Kerja Di Industri Pembuatan Sepatu ”X” Kota Semarang Berdasarkan Prinsip 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) - - Fathimah; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2014)
5S is a culture about how people treat their workplace properly. If the workplace neat, clean, and orderly, then the ease of individual works can be created, and thus the 4 main targets industrial fields, namely efficiency, productivity, quality, and include safety and health that would be more easily achieved. Basically 5S is a process change in attitude by applying the arrangement and cleanliness of work, or in general is the Occupational Health and Safety ( K3 ). Based on a survey early, workers in this industry still not apply 5S in any stage of the work they do. This is evident from the less organized neat working environment there. The purpose of this study was analyze the arrangement of workplaces in the shoe-making industry "x" in Semarang City based on the principles of 5S. This research is an action research study linking theory with practice. Population in this research is workers in the shoe-making industry "x" as much as 8 workers. Analysis of data used is qualitative using a process of inductive. The results of this study showed that workers in the industry do not know the knowledge of 5S and also did the arrangement based on the principles of 5S workplace. Moreover, even this industry there are no facilities that support the neatness and cleanliness of the workplace. The evaluation results are obtained there were no significant changes to the arrangement of the workplace in the industry. From this study it can be concluded that all workers in this industry have yet to implement good workplace arrangement based on the principles of 5S